2019
DOI: 10.1111/ijac.13268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2addition on microstructure and mechanical properties of alumina‐based cores prepared by sol‐gel method

Abstract: Alumina-based ceramic cores have widespread applications especially in the investment casting of turbine blades due to chemical inertness with most of the superalloys, capability of machining in the green state, and their mechanical stability at high temperatures. The present work studied the effects of TiO 2 addition to the alumina-based cores. These cores were prepared via the sol-gel method process by mixing alumina powders with NH 4 Cl and silica sol. The effects of adding different amounts of titania from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Solar cell based on a dye‐sensitized porous nanocrystalline TiO 2 photoanode with attractive performance was first reported by Grätzel et al By the application of Nanoporous TiO 2 , the effective surface area can be enhanced 1000‐fold. An intriguing feature in the Nanocrystalline TiO 2 film is that the charge transport of the photo‐generated electrons passing through all the particles and grain boundaries is highly efficient …”
Section: Introductionmentioning
confidence: 99%
“…Solar cell based on a dye‐sensitized porous nanocrystalline TiO 2 photoanode with attractive performance was first reported by Grätzel et al By the application of Nanoporous TiO 2 , the effective surface area can be enhanced 1000‐fold. An intriguing feature in the Nanocrystalline TiO 2 film is that the charge transport of the photo‐generated electrons passing through all the particles and grain boundaries is highly efficient …”
Section: Introductionmentioning
confidence: 99%
“…22 The result showed that YAG was homogeneously distributed among the alumina grains. 24 In comparison, the alumina-based ceramic cores doped with yttrium oxide have a smaller linear shrinkage. As a result, some pores are occupied by YAG particles, causing the microstructure of ceramic cores to become dense.…”
Section: Resultsmentioning
confidence: 99%
“…Under the same sintering conditions, the linear shrinkages of alumina-based ceramic cores doped with different amounts of yttrium oxide are lower than 0.5%; however, the linear shrinkages of alumina-based ceramic cores doped with different amounts of TiO 2 are higher than 3%. 24 In comparison, the alumina-based ceramic cores doped with yttrium oxide have a smaller linear shrinkage. Figure 7A,B show the relative density and apparent porosity of Al 2 O 3 -based ceramic cores.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they should be characterized by a good phase stability at high temperature, as well as a flexural strength above 20 MPa at the casting temperature of the metal alloy. Moreover, a porosity of at least 30% is required to facilitate the chemical dissolution of the ceramic component after casting (Qin and Pan, 2009;Shabani et al, 2019).…”
Section: Space and Aerospace Applicationsmentioning
confidence: 99%